TINJAUAN SOSIOLOGIS RELASI KUASA ANTARA DOKTER DENGAN PASIEN DI BEBERAPA RUMAH SAKIT KOTA DENPASAR - Sinaga, Willyam Steven; Nugroho, Wahyu Budi; Sastri Mahadewi, Ni Made Anggita (JURNAL ILMIAH SOSIOLOGI (SOROT), 2021)
Power relations are relationships, patterns and systems created by the existence of power. As is the case in other professions, the potential for power relations that occur between doctors and patients is certainly influenced by knowledge, discourse and power which is dominated by doctors. Based on the results of this study, the relationship that exists between doctors and patients is no longer always between the subject and the object. In the current information age, patients can access health information from various media so that various doctor's recommendations can be considered as a whole. This study also explains how to analyze the impact of knowledge discourse in the information age that can affect the power relations between doctors and patients at A Hospital, B Hospital and C Hospitals. Keywords: Power Relations, subject & object, Hospital in Denpasar, Analysis, Impact